The effect of different sports specialization on ankle joint mobility of young players - Francia, P.; Bocchi, L.; Santosuosso, U.; Iannone, G.; Vittori, A.; Toni, S. (Journal of Human Sport & Exercise, 2021)
The aim of the study was to investigate the effects of practicing different sports on ankle joint mobility (AJM) in young subjects. In 344 players of 5 different sports (soccer, classical ballet, gymnastics, volleyball and basketball), mean age 12.0 ± 2.4 years, sex (male/female: 237/107), BMI 19.0 ± 2.8 (Kg/m2), AJM was evaluated by using an inclinometer while the trunk flexibility was evaluated by the Sit and Reach test. Compared to all other groups, soccer players showed a significant reduction of AJM (p < .005) that is already present in younger subjects and that tends to worsen with aging (p < .04). On the contrary, the young dancers of classic ballet showed a significant increase in the AJM (p < .002). Basketball, volleyball and gymnastics groups showed a similar AJM. The higher AJM showed by females compared to males (128.5 ± 21.0° vs 144.6 ± 18.5°; p < .001) was not significant when the group of soccer players and dancers were excluded from the calculation. All groups investigated did not show a different mobility between the two ankles or the dominant and non-dominant limb. The age of the subjects investigated was not correlated with AJM. The group of gymnasts showed a significant increase in trunk flexibility (p < .001) compared to all other groups. Sport practice can significantly modify AJM both by increasing and reducing it. Such process should be timely assessed in order to prevent these alterations along with the related possible negative effects in the short and long term.